N-terminal proatrial natriuretic peptide correlates with systolic dysfunction and left ventricular filling pattern in patients with idiopathic dilated cardiomyopathy. Issue 5 (1st November 1999) - Fruhwald, F M; Fahrleitner, A; Watzinger, N; Dobnig, H; Schumacher, M; Maier, R; Zweiker, R; Leb, G; Klein, W
Abstract : OBJECTIVE: To investigate the diastolic Doppler filling pattern in patients with idiopathic dilated cardiomyopathy and its relation to N-terminal pro-atrial natriuretic peptide (NT-pro-ANP). METHODS: 32 patients (26 male, six female) with idiopathic dilated cardiomyopathy were investigated. All were in sinus rhythm. Conventional M mode echocardiography and Doppler echocardiography was done in each patient. Pulsed wave Doppler inflow signals were obtained and the following variables were measured: maximum E wave, maximum A wave, E/A ratio, E wave deceleration time, A wave deceleration time. NT-pro-ANP was measured using radioimmunoassay. RESULTS: Mean (SD) left ventricular ejection fraction was 34 (7)% and mean left ventricular end diastolic diameter on M mode echocardiography was 69 (7) mm. Left ventricular filling indices were as follows: maximum E wave velocity, 0.86 (0.22) m/s; maximum A wave velocity, 0.71 (0.24) m/s; E/A ratio, 1.41 (0.65). Mean E wave deceleration time was 140 (50) ms; mean A wave deceleration time was 100 (20) ms. In a stepwise forward regression model, NT-pro-ANP correlated significantly with left atrial diameter ( r = 0.603; p < 0.001), left ventricular ejection fraction ( r = −0.758; p < 0.001), and Doppler derived E/A ratio ( r = 0.740; p < 0.001). CONCLUSIONS: In patients with idiopathic dilated cardiomyopathy there is a relation between NT-pro-ANP and both systolic and diastolic variables. In a multivariate model NT-pro-ANP correlated with left atrial diameter, left ventricular ejection fraction, and Doppler derived E/A ratio on transmitral inflow.